Teoria da agência aplicada à gestão patrimonial: estudo na Universidade Federal do Tocantins - Oliveira, Adriano Xavier de (2021)
The Federal University of Tocantins Foundation (UFT) is a public institution that must execute the proper management and control of its assets to prevent damage or loss. In this sense, in the relationships that involve the UFT as the owner of the assets, the departments responsible for managing its assets and the servants who hold the custody of the permanent materials, different agency conflicts may arise. The aim of this study was to analyze the agency conflicts existing in the asset management process at the Federal University of Tocantins and understand how the relationship between the departments responsible for this management occurs. In order to achieve this objective, the elements that are part of asset management in the public sector were verified and how this routine is structured in the UFT; the main bottlenecks in UFT's asset management were identified; agency conflicts between the departments responsible for managing the institution's assets and their respective causes were identified; and possible improvements to the university's asset management were proposed that could minimize existing agency conflicts. The relevance of the research lies in the search for improving asset management, which results in a better use of public money, and also in the fact that there is a shortage of papers dealing specifically with the themes: Agency Theory and asset management. This was an exploratory descriptive research, as the methodological strategies adopted encompassed different methods so that the objectives outlined for this study could be achieved. As for the type of approach, the present investigation had a quantitative and qualitative character. As for the technical procedures, bibliographical, documental and field research were carried out. The objectives are considered to have been met. It was possible to verify the elements that are part of asset management in the public sector in general, as well as to map and describe the activities that make up UFT's asset management. Eleven (11) bottlenecks were identified in the asset management of the institution under study, as well as 3 (three) agency conflicts between the departments responsible for managing the institution's assets. Based on the identified problems, proposals were made to improve the university's asset management in order to minimize existing agency conflicts. If the proposed suggestions are implemented, the management of the institution's important set of material resources, which is its assets, can be improved. However, the research recommendations have limitations and do not dispense the evaluation of university managers regarding the convenience and feasibility of application.